Hiện trạng thị trường thông tin khoa học và công nghệ thế giới - Cao, Minh Kiểm (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Explains the concept of  STI market and indicates clearly  kinds of commodities in this market; describes the state of the art of STI market in the world, underlining aspects: S&T documents, on-line STI services, S&T bibliographical information services, and the content of on-line science and technology.